2016
DOI: 10.1016/j.pharep.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Epicutaneous (EC) immunization with type II collagen (COLL II) induces CD4 + CD8 + T suppressor cells that protect from collagen-induced arthritis (CIA)

Abstract: Maneuver of EC immunization with a protein antigen that induces suppressor cells to inhibit inflammatory responses may become an attractive, noninvasive, needle-free therapeutic method for different clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It has been well documented that CD4 + T cells are required for the induction of CIA, whereas CD8 + T cells exhibit a suppressive role (38,39). The proportion of CD4 + T cells was significantly increased, whereas the proportion of CD8 + T cells was decreased in patients with RA (40). Consistent with these facts, our results showed that GdX-KO mice under CII treatment developed less inflammation with fewer CD4 + T cells and more CD8 + T cells, whereas the WT CIA mice owned reversed populations of T cells.…”
Section: Discussionmentioning
confidence: 98%
“…It has been well documented that CD4 + T cells are required for the induction of CIA, whereas CD8 + T cells exhibit a suppressive role (38,39). The proportion of CD4 + T cells was significantly increased, whereas the proportion of CD8 + T cells was decreased in patients with RA (40). Consistent with these facts, our results showed that GdX-KO mice under CII treatment developed less inflammation with fewer CD4 + T cells and more CD8 + T cells, whereas the WT CIA mice owned reversed populations of T cells.…”
Section: Discussionmentioning
confidence: 98%
“…According to a 5-point scale, the Arthritis index (AI) was calculated as follows: 0 = no evidence of erythema and swelling; 1 = mild erythema and swelling of the wrist or ankle; 2 = moderate erythema and swelling from the wrist to the metacarpal joints or from the ankle to the metatarsal joints; 3 = severe erythema and swelling of the entire paw including the digits and 4 = maximal erythema and swelling of the paw, or ankylosis of the limb. The total AI was the sum of the scores for each of the four limbs (Marcinska et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…A recent clinical trial showed reduced signs of disease activity in relapsing–remitting MS patients treated with a transdermal application of a mixture of myelin peptides containing MBP85-99, MOG35-55, and PLP139-155 ( 21 ). Efficacy of specific skin-induced tolerance was also demonstrated in collagen-induced arthritis ( 22 ) and inflammatory bowel disease ( 23 ). The effectiveness of these strategies has been correlated with the presence of tolerogenic dendritic cells (DCs) and Tregs expansion.…”
Section: Introductionmentioning
confidence: 99%